Association of smoking with indicators of the structure and function of left ventricle of the heart in middle-aged men - O. Yu. Isaykina; V. B. Rozanov; A. A. Aleksandrov; M. B. Kotova; M. A. Isaykina; O. M. Drapkina (Столичная издательская компания, 2021)
Aim. Evaluation of the association of smoking (status, intensity and duration) with indicators of the structure and function of the left ventricle of the heart in a sample of middle-aged men.Material and methods. This study is part of a 32-year prospective cohort observation of men from childhood (11-12 years). 301 (30.0%) representatives of the original population sample aged 41-44 years were included in the study. The examination included a survey on intensity of smoking, anthropometry, measuring blood pressure, pulse rate, echocardiography, and blood lipid analysis.Results. 301 men aged 41-44 included 92 (30.6%) men who had never smoked, 73 (24.3%) men smoked in the past and 136 (45.2%) men currently smoke. 75% of current smokers started smoking before age 19, of which 32.3% started smoking before age 15. The duration of smoking cessation among former smokers was 14.4 (12.5; 16.2) years. The average duration of smoking [average (95% confidence interval)] among former smokers was 14.4 (12.5; 16.2), for current smokers - 25.3 (24.6; 26.0) years. Current smoking was statistically significantly associated with higher mean values of the left ventricular myocardium mass (LVMM), the left ventricular myocardial mass index (LVMMI), the end-systolic and end-diastolic interventricular septum thickness (IVSTs/IVSTd), the end-systolic left ventricular posterior wall thickness (LVPWs), and the intensity and duration of current smoking were associated with higher values of the relative wall thickness of the left ventricle, the end-diastolic interventricular septum thickness, the end-systolic interventricular septum thickness, and with low values of the left ventricular stroke volume index (LV SVI). Multiple regression analysis showed that current smoking has an independent effect on the left ventricular myocardium mass, the left ventricular myocardial mass index and the end-diastolic interventricular septum thickness, and the duration and intensity of smoking has an effect on the index of the left ventricular stroke volume index.Conclusion. Current smoking, duration and intensity in middle-aged men is associated with unfavorable changes in indicators of the structure and function of the left ventricle of the heart. Efforts for primary prevention of smoking should begin as early as childhood and continue into adolescence and young adulthood.